2005
DOI: 10.1508/cytologia.70.161
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Studies on Four Egyptian Scorpion Species of Genus Androctonus (Family: Buthidae)

Abstract: Summary Chromosomal analysis of 4 Egyptian species of family Buthidae (Androctonus australis, Androctonus bicolor, Androctonus amoreuxi and Androctonus crassicauda) have been studied. The 4 buthid scorpions species have the same diploid chromosome number of 2nϭ24. These species have a unique combination of cytogenetic features including holocentric chromosomes. Multivalent chromosomes of regular and irregular form were observed during the first meiotic division. To the best of the authors knowledge, these resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…The diploid number of buthids varies from 2n=5 to 2n=56, and the presence of holocentric chromosomes seems to be a shared characteristic among all species studied to date (Schneider et al 2009). Similar to other scorpions, two chromosomal features in Buthidae were observed in male meiosis: multivalent associations in heterozygous for reciprocal translocations and achiasmate behaviour of the chromosomes (Piza 1947a(Piza , b, 1948a(Piza , b, c, 1957Sharma et al 1959;Gupta and Sarker 1965;Shanahan 1989a;Moustafa et al 2005). According to Shanahan (1989a), Buthidae is an uncommon taxon among animals because it has a combination of both holocentric chromosomes and heterozygous translocations.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The diploid number of buthids varies from 2n=5 to 2n=56, and the presence of holocentric chromosomes seems to be a shared characteristic among all species studied to date (Schneider et al 2009). Similar to other scorpions, two chromosomal features in Buthidae were observed in male meiosis: multivalent associations in heterozygous for reciprocal translocations and achiasmate behaviour of the chromosomes (Piza 1947a(Piza , b, 1948a(Piza , b, c, 1957Sharma et al 1959;Gupta and Sarker 1965;Shanahan 1989a;Moustafa et al 2005). According to Shanahan (1989a), Buthidae is an uncommon taxon among animals because it has a combination of both holocentric chromosomes and heterozygous translocations.…”
Section: Introductionmentioning
confidence: 90%
“…On the other hand, there is a hypothesis that holocentric chromosomes gave rise to monocentrics, which are defined by kinetic activity restricted to a specialised chromosome region known as the centromere (Moore et al 1997). In arachnids, chromosome with nonlocalised centromere had multiple and independent origin, taking into account that it was observed in different groups not closely related, such as mites (Wrensch et al 1994), spiders of the superfamily Dysderoidea (Král et al 2006), and scorpions of the family Buthidae (Piza 1947a(Piza , b, 1950Gupta and Sarker 1965;Benavente 1982;Shanahan 1989a;Moustafa et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the genome size of the scorpion M. martensii Karsch was estimated to be approximate 600 Mbp. Although the chromosome numbers of several species in the order Scorpiones are known (Moustafa et al, 2005), the genome size of any scorpion species has not been reported previously. Compared with that of the other arthropods, the C-value 1.19 pg of the scorpion M. martensii Karsch is very small, e. g., Cvalues of the spiders set range from 0.74 pg to 5.7 pg (Gregory, 2005;Gregory and Shorthouse, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…A review showed that only about 80 of over 2000 known species of scorpions have been evaluated by chromosome studies (Moustafa et al 2005, Schneider et al 2009). We recently reported the karyotypes of three species from Palestine: Leiurus quinquestriatus, Hottentotta judaicus, and Scorpio maurus fuscus (Qumsiyeh et al 2013).…”
mentioning
confidence: 99%
“…We recently reported the karyotypes of three species from Palestine: Leiurus quinquestriatus, Hottentotta judaicus, and Scorpio maurus fuscus (Qumsiyeh et al 2013). The only other study of chromosomes in the Middle East was done in Egypt of some members of the genus Androctonus, which had a fairly uniform 2n=24 (Moustafa et al 2005).…”
mentioning
confidence: 99%